Training repeated effort ability in national team male volleyball players - Sheppard, J. M.; Gabbett, T. J.; Borgeaud, B. (International Journal of Sports Physiology and Performance, 2008)
Purpose: This case study evaluated the effect of repeated lateral movement and jumping training on repeated effort ability in a group of national team male volleyball players. Methods: Twelve volleyball players were assessed on their volleyball-specific repeated movement and jumping abilities using a volleyball-specific repeated effort test (RET) before and after 12 weeks of training. The athletes performed between 8 and 9 volleyball training sessions per week, with 5 to 6 of these sessions including specific training aimed at improving repeated effort ability. Typically these training sessions involved 8 to 12 repetitions of 2 to 3 block jumps over a 9-m lateral distance (ie, the athletes had to perform jumps and lateral movements, typical of front court play in volleyball). Population-specific repeatability data were used to determine whether any changes that may have occurred in this study were beyond the minimal clinically important difference (MCID) for this testing procedure. Results: Improvements in all variables of the RET were observed for each athlete involved in the study, with a small-to-moderate magnitude observed for the mean changes in each variable (Cohen`s d, 0.21 to 0.59). All of the improvements in the results exceeded the MCID. Conclusions: These findings demonstrate that the RET is sensitive to training-induced changes. Lateral movement speed and repeated lateral movement speed, as well as jumping and repeated jumping ability are trainable qualities in high-performance volleyball players.